MEASUREMENT OF THE TRANSVERSE CURRENT IN THE MAGNETIC CAGE ROTOR ASYNCHRONOUS MOTORS - , Г. В., В. Б., Я. Б. (Municipal economy of cities. Series: «Economy science», 2013)
The experimental measurement of the transverse current in the magnetic cage rotor induction motor at the elementary area in the short-circuit.